2004
DOI: 10.4269/ajtmh.2004.70.302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to Hantavirus Among Family and Health Care Worker Contacts of Persons With Hantavirus Cardiopulmonary Syndrome: Lack of Evidence for Nosocomial Transmission of Andes Virus to Health Care Workers in Chile

Abstract: Nosocomial transmission of Andes virus has been documented in Argentina, but has not yet been proven in Chile. We studied 215 contacts (106 family member contacts and 109 health care worker contacts) of 20 index cases of hantavirus cardiopulmonary syndrome (HCPS) in Chile. The seroprevalence of IgG antibodies against Andes virus was 1.9% (95% confidence interval [CI] = 0.34-6.3%) among the family members and 0.0% (95% CI = 0-3.2%) among the health care workers. Our data suggest that there is no evidence for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
(16 reference statements)
0
16
0
4
Order By: Relevance
“…Second, the number of days from exposure to an index case-patient and the onset of symptoms among additional cases ranges from 12 to 27 days ( 7 , 26 ), consistent with the intervals observed in our report. In the 2 cases for which environmental exposure was reported, the estimated incubation period after that exposure exceeded the longest reported incubation range of 42 days for ANDV ( 3 , 11 ). In contrast, in these 2 cases the estimated incubation periods from exposure to a case-patient to onset of symptoms was 13–27 days.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Second, the number of days from exposure to an index case-patient and the onset of symptoms among additional cases ranges from 12 to 27 days ( 7 , 26 ), consistent with the intervals observed in our report. In the 2 cases for which environmental exposure was reported, the estimated incubation period after that exposure exceeded the longest reported incubation range of 42 days for ANDV ( 3 , 11 ). In contrast, in these 2 cases the estimated incubation periods from exposure to a case-patient to onset of symptoms was 13–27 days.…”
Section: Discussionmentioning
confidence: 87%
“…IgM and IgG seroconversion were confirmed 10 days after symptom onset. The person-to-person exposure period for this patient was March 6–20; his possible environmental exposure exceeded the known incubation period for ANDV ( 11 ). Shock and respiratory failure developed, and he required mechanical ventilation and vasopressors but survived.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Prevalence in Venezuela was 1.7% 24 ; in northeastern Argentina, seroprevalence was 6.5% and was statistically significant for rural activity compared to other studies 25 ; while Chile showed a seroprevalence of 1.9% among family members of patients with HPS [25][26][27] . The highest prevalence occurred in Paraguay, with a mean of 42.7%, and the risk of infection was higher among those who lived in rural environments, similar to the present study 21,27 .…”
Section: Conflict Of Interest Referencesmentioning
confidence: 89%
“…Fortunately, none of the persons exposed to the patient reported symptoms consistent with HPS during the incubation period, and none who were tested seroconverted. Seroprevalence surveys in Chile among healthcare worker contacts of patients with HPS caused by the Andes virus showed a prevalence of 0% ( 9 ). A report from Argentina showed that cases due to secondary transmission occurred mostly in non-healthcare workers after prolonged close contact in the prodromal period ( 10 ).…”
mentioning
confidence: 99%